NOSTALGIA AS AN OBJECT OF SOCIOLOGICAL STUDY: ISSUES AND THEORETICAL APPROACHES - Birškytė, Lina (Sociologija. Mintis ir veiksmas, 2016)
Nostalgia defined as a social phenomenon is an object of this article. The article discusses theoretical nostalgias interpretations and analyses various forms in which nostalgia manifests itself. Author emphasizes a necessity to distinguish between modern and post-modern nostalgias. Modern nostalgia has been conceptualised as yearning for the past. This yearning originates from a disappointment with contemporary life and disapproval of permanent progress idea. However, post-modern nostalgia does not involve sentiments or melancholia. Contemporary culture, characterised by mediated culture, mass production and consumption, creates preconditions for new forms of nostalgia. Idealized images of the past are being used for commercial purposes and retrospective artefacts become tools for creating style and looks. In addition, author criticizes the term “soviet nostalgia” and suggests “nostalgia for socialism” to be used instead. Ostalgia, as the most studied form of nostalgia for socialism, is being discussed with an emphasis on distinction between its modern and post-modern manifestations.
Keywords: nostalgia; postmodern nostalgia; nostalgia for socialism; ostalgie